The Effect Of âPLANSâ Training Towards Career Maturity Of Senior High School Students - Hidayat, Muhammad; Alsa, Asmadi (Journal of Educational, Health and Community Psychology, 2018)
Career maturity is defined as the maturity of attitudes and competencies related to career decision making. Based on the problems found in preliminary studies showed that many students of class XII were confused in the selection of majors for advanced study at university . This suggests that many students of class XII who has a career that is still lacking maturity . PLANS training was given to students of class XI N tutoring with the goal of improving career maturity . The hypothesis of this study was PLANS training to increase the maturity of career guidance to students studying in class XI N . The experiment design used Untreated Control Group Design with Dependent Pretest and Posttest Samples. In this study, the independent variable is PLANS training , while the dependent variable is the career maturity . Training subjects were 30 students ( 15 experimental group and 15 control group ) . Scale research instrument is the attitude of career maturity and career maturity competency test . Results of ANOVA analysis of the mixture showed a change from pretest to posttest scores were significant in the experimental group and the control group there was no significant change . The contribution of this training is equal to 40.4 % for the attitude domainÂ  and 62.5 % for the domain of career maturity competence.